Optimizing the Reactivity of Surface Confined Cobalt N4- Macrocyclics for the Electrocatalytic Oxidation of L-Cysteine by Tuning the Co(Ii)/(I) Formal Potential of the Catalyst - Zagal-Moya, J; Zagal-Moya, J; Pavez-Irrazabal, J; Pavez-Irrazabal, J; Gulppi-Cabra, M; Gulppi-Cabra, M; Silva-Rojas, J; Silva-Rojas, J; Recio-Cortes, F; Recio-Cortes, F; Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier Ltd, 2014)
The redox potential of macrocyclic complexes is a very predictive reactivity index for the electrocatalytic activity of these molecules and it can be easily measured under the same conditions of the kinetic experiments. It reflects directly the catalytic activity of a given complex. We have investigated the effect of the Co(II)/(I) formal potential of CoN4 macrocyclics complexes on the catalytic activity of a series of Co porphyrins and Co phthalocyanines for the electrooxidation of l-cysteine. The complexes were adsorbed on ordinary pyrolytic graphite. A correlation of log i (at constant potential) versus the Co(II)/(I) formal potential of the catalysts gives a volcano curve. Our results clearly show that the Co(II)/(I) formal potential of N4-macrocyclic complexes needs to be adjusted to values around -0.96 V vs. SCE to obtain the highest catalytic activity for the oxidation of l-cysteine at pH 13. © 2013 Elsevier Ltd.